2017
DOI: 10.1016/j.diff.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate regulates chondrogenesis in a biphasic and maturation-dependent manner

Abstract: Inorganic phosphate (Pi) has been recognized as an important signaling molecule that modulates chondrocyte maturation and cartilage mineralization. However, conclusive experimental evidence for its involvement in early chondrogenesis is still lacking. Here, using high-density monolayer (2D) and pellet (3D) ATDC5 chondrogenic models treated with ITS+, β-glycerophosphate (βGP), or ITS+/βGP, we demonstrate that the cell response to Pi does not correlate with the Pi concentration in the culture medium but is bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Based on these results, we fabricated a multi-well device allowing for stable spheroid formation from a large number of ATDC5 cells (3 × 10 5 cells/well). The number of ATDC5 cells required for spheroid formation was comparable to a previous report which produced 3D micromass pellet from 2.5 × 10 5 cells (Wu et al 2017). Furthermore, the spheroid formation in our devices showed a high reproducibility sequential process similar to that observed during chondrocyte differentiation (Atsumi et al 1990), it has been used as a suitable in vitro cell culture model to elucidate the mechanisms of chondrogenesis, including the demonstration of the ideal biomimetic microenvironment for chondrogenesis in 3D spheroid cultures.…”
Section: Discussionsupporting
confidence: 82%
“…Based on these results, we fabricated a multi-well device allowing for stable spheroid formation from a large number of ATDC5 cells (3 × 10 5 cells/well). The number of ATDC5 cells required for spheroid formation was comparable to a previous report which produced 3D micromass pellet from 2.5 × 10 5 cells (Wu et al 2017). Furthermore, the spheroid formation in our devices showed a high reproducibility sequential process similar to that observed during chondrocyte differentiation (Atsumi et al 1990), it has been used as a suitable in vitro cell culture model to elucidate the mechanisms of chondrogenesis, including the demonstration of the ideal biomimetic microenvironment for chondrogenesis in 3D spheroid cultures.…”
Section: Discussionsupporting
confidence: 82%
“…Continuing stimulation with the OM might decrease chondrogenic differentiation and instead induce matrix mineralization. Wu et al, 34 also observed this when stimulating ATDC5 cells with β-glycerophosphate; they confirmed early chondrogenesis with an upregulation of COL2 and ACAN and the production of a GAGrich matrix within the first 7 days. Beta-glycerophosphate delivery after early chondrogenesis further upregulated hypertrophic markers.…”
Section: Discussionmentioning
confidence: 75%
“…Beta-glycerophosphate delivery after early chondrogenesis further upregulated hypertrophic markers. 34 GAG content was significantly higher in AFCs and CEPCs stimulated with BM + BMP2 and L51P than in BM control treatment. The same was observed for DNA content.…”
Section: Discussionmentioning
confidence: 80%
“…To assess the accumulation of cartilage-specific matrix in both 2D and 3D cultures, the level of sGAG of each sample was quantified using DMMB assay as previously described 25,29 . Specifically, differentiated cell masses from 2D cultures or pellets from 3D cultures were washed with ice-cold PBS before being digested with 1mg/ml proteinase K in 200-500µl ammonium acetate (0.1M) at 50°C for 16 hours.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…6a and Fig. S1): minimum RUNX2 protein expression (D4), just prior to rapid increase in RUNX2 protein expression (D7), peak gene expression of Col10a1 (D14) 25 , and the peak of RUNX2 protein expression (D21). These were compared to cultures that received no Dox or were treated with Dox from day 0 (D0).…”
Section: Stage-dependent Effect Of Runx2 Silencing On Chondrogenesismentioning
confidence: 99%